Theta-Burst Stimulation for Cognitive Enhancement in Parkinson's Disease With Mild Cognitive Impairment: A Randomized, Double-Blind, Sham-Controlled Trial - Lang, Stefan; Gan, Liu Shi; Yoon, Eun Jin; Hanganu, Alexandru; Kibreab, Mekale; Cheetham, Jenelle; Hammer, Tracy; Kathol, Iris; Sarna, Justyna; Martino, Davide; Monchi, Oury (Frontiers in Neurology, 2020)
Background: Mild cognitive impairment is a common non-motor symptom of Parkinson’s disease (PD-MCI) and has minimal treatment options. Objective: In this double-blind, randomized, sham-controlled trial, we assessed the effect of repeated sessions of intermittent theta-burst stimulation (iTBS) over the left dorsolateral prefrontal cortex (DLPFC) on cognition and brain connectivity in subjects with PD-MCI. Methods: 41 subjects were randomized to receive real (n = 21) or sham stimulation (n = 20). All subjects underwent neuropsychological assessments before, one day, and one month after stimulation. Subjects also underwent resting-state fMRI before and 48 hours after stimulation. The primary outcome was the change in cognitive domain (executive function, attention, memory, language, and visuospatial abilities) z-scores across time. Results: There was an insignificant effect on cognitive domain z-scores across time when comparing real to sham stimulation and correcting for multiple comparisons across cognitive domains (p>0.05 Bonferroni correction). However, the real stimulation group demonstrated a trend toward improved executive functioning scores at the one-month follow-up compared to sham (p<0.05 uncorrected). Following real stimulation, the connectivity of the stimulation site showed decreased connectivity to the left caudate head. There was no change in connectivity within or between the stimulation network (a network of cortical regions connected to the stimulation site) and the striatal network. However, higher baseline connectivity between the stimulation network and the striatal network was associated with improved executive function scores at one month. Conclusions: These results suggest that iTBS over the DLPFC in subjects with PD-MCI has minimal effect on cognition compared to sham, though there were trends towards improved executive function. This intervention may be more effective in subjects with higher baseline connectivity between the stimulation network and the striatal network. This trial supports further investigation focusing on executive function and incorporating connectivity based targeting.